Implementation of the energy efficiency existing ship index and carbon intensity indicator on domestic ship for marine environmental protection - Chuah, Lai Fatt; Mokhtar, Kasypi; Mhd Ruslan, Siti Marsila; Abu Bakar, Anuar; Abdullah, Mohd Azhafiz; Osman, Nor Hasni; Bokhari, Awais; Mubashir, Muhammad; Show, Pau Loke (Elsevier, 2023)
The International Maritime Organization has set a goal to achieve a 50% reduction of total annual greenhouse gas emission related to the international shipping by 2050 compared to the 2008 baseline emissions. Malaysia government has taken an initiative to investigate the assessment (cost-effectiveness) of this International Maritime Organization's short-term measure on Malaysian-registered domestic ships although this measure is only for international merchant ship. To achieve this, this paper collected the ship's data from the shipowners from 25 sample ships. Engine power limitation is the most cost-effective option, but low power limits can lead to substantially increased sailing times. Based on cost-efficiency analysis, it creates for the purpose of compliance with the operational carbon intensity indicator. It found that even if it is possible to bring an asset back into service, it may not be possible to do so in a manner that generates a profit or complies with applicable regulations. In these situations, it may be more prudent to scrap the asset rather than run the risk of having it become a stranded asset. This is especially true for older tankers. Alternatives with lengthy payback periods are not desirable for the domestic tanker fleet that is already in operation